2020
DOI: 10.1093/intimm/dxaa073
|View full text |Cite
|
Sign up to set email alerts
|

Aicardi–Goutières syndrome-like encephalitis in mutant mice with constitutively active MDA5

Abstract: MDA5 is a cytoplasmic sensor of viral RNA, triggering type-I interferon (IFN-I) production. Constitutively active MDA5 has been linked to autoimmune diseases such as systemic lupus erythematosus, Singleton–Merten syndrome (SMS), and Aicardi-Goutières syndrome (AGS), a genetically determined inflammatory encephalopathy. However, AGS research is challenging due to the lack of animal models. We previously reported lupus-like nephritis and SMS-like bone abnormalities in adult mice with constitutively active MDA5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…MDA5 is also a cytosolic dsRNA receptor. MDA5 has been shown to play a role in autoimmune diseases such as inflammatory encephalopathy and Aicardi-Goutieres syndrome where microglia are activated and show increased phagocytosis ( Onizawa et al, 2021 ). The precise expression pattern and function of these two dsRNA sensors is still poorly understood in microglia.…”
Section: Discussionmentioning
confidence: 99%
“…MDA5 is also a cytosolic dsRNA receptor. MDA5 has been shown to play a role in autoimmune diseases such as inflammatory encephalopathy and Aicardi-Goutieres syndrome where microglia are activated and show increased phagocytosis ( Onizawa et al, 2021 ). The precise expression pattern and function of these two dsRNA sensors is still poorly understood in microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Seven gene mutations, including TREX1, RNASEH2B, and RNASEH2C have been identified to cause AGS (Rice et al, 2013). The lack of a reliable animal model of AGS hinders the research of disease physiology and treatment (Onizawa et al, 2021). Therefore, when Thomas et al used iPSCs derived from AGS patients to study brain organoids, they found many nerve cell death and nerve cell inflammation, which is similar to clinical neurodegeneration and eventually leads to microcephaly (Thomas et al, 2017).…”
Section: Microcephalymentioning
confidence: 99%
“…Pathological signs are associated with increased type I interferon (IFN-α) activity and lymphocytosis in the cerebrospinal fluid and serum and activation of IFN-related downstream signaling [ 142 ]. Astrocytes are the major source of IFN-α in CNS; thus, they were recently proposed as the main players in AGS pathogenesis [ 44 ], though their contribution to the myelin/oligodendrocyte damage is still not clarified [ 52 , 143 ]. Current hypotheses on astrocyte-driven AGS myelin deficits are that mutated, suffering astrocytes are no longer able to support survival/proliferation and myelination capacity of oligodendrocytes and that mutated, activated astrocytes negatively influence OPC maturation due to the detrimental release of IFN-α and inflammatory cytokines [ 139 ].…”
Section: Astrocytopathies: When Myelin Defects Are Caused By Astrocyte Disfunctionsmentioning
confidence: 99%
“…To study AGS pathogenesis, many cellular and animal models were developed ( Figure 5 ), including several null mice for the genes involved in AGS (KO), mice expressing the human mutations (KIN) ( TREX1 KO and KIN, RNASEH2A/B/C KO, RNASEH2A/B KIN, SAMHD1 KO, ADAR1 KO, IFIH1 KIN) and some zebrafish models ( SAMDH1 and ADAR1 KO). However, many of these models showed embryonic lethality, while the other did not have an overt brain phenotype ([ 33 ] and references therein) [ 143 ]. Indeed, lab mice live in relatively sterile environments and lack the initial viral stimulus that may trigger the type I interferon response, condition that can explain the absence of neuroinflammation in these animals [ 33 ].…”
Section: Astrocytopathies: When Myelin Defects Are Caused By Astrocyte Disfunctionsmentioning
confidence: 99%